2020
DOI: 10.1109/access.2020.2972265
|View full text |Cite
|
Sign up to set email alerts
|

SHA-2 Acceleration Meeting the Needs of Emerging Applications: A Comparative Survey

Abstract: While SHA-2 is a ubiquitous cryptographic hashing primitive, its role in emerging application domains, e.g. blockchains or trusted IoT components, has made the acceleration of SHA-2 very challenging due to new stringent classes of requirements, especially implementation cost and energy efficiency. The survey discusses these emerging applications and their fundamental requirements. Then, the work presents a comprehensive review of the different design techniques available in the literature for SHA-2 acceleratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…These works used a hardware description language (HDL) to implement the SHA-256 core and package it as an IP core [21]. Martino et al [22] survey acceleration techniques of SHA-2 at the architectural abstraction level and summarized their impact on logic area, energy, and power consumption. However, none of these works analyzed the use of a high level coding style such as OpenCL to generate an FPGA-based SHA-2 since the previously published optimization cannot be applied at the OpenCL-level.…”
Section: Related Workmentioning
confidence: 99%
“…These works used a hardware description language (HDL) to implement the SHA-256 core and package it as an IP core [21]. Martino et al [22] survey acceleration techniques of SHA-2 at the architectural abstraction level and summarized their impact on logic area, energy, and power consumption. However, none of these works analyzed the use of a high level coding style such as OpenCL to generate an FPGA-based SHA-2 since the previously published optimization cannot be applied at the OpenCL-level.…”
Section: Related Workmentioning
confidence: 99%
“…In [44] the authors discussed the relevance of EC based on the algebraic structure of a curve over a finite field in modern applications. In [45], the authors suggested that Secure Hash Algorithms (SHA) require optimization and a hybrid of multiple techniques based on the underlying application. A comparison of the SHA family of algorithm as displayed in Table 3 based on security standards reveals the functional, security level, and block size.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A comparison of the SHA family of algorithm as displayed in Table 3 based on security standards reveals the functional, security level, and block size. As derived from [45], the use of SHA in various application as displayed in Table 4 highlights the importance of SHA algorithms for use in IoT and blockchain. Note: Comparison taken from [45] In this section, a literature review of LSB, Blockchainbased IoT applications, traditional IoT security measures, lightweight blockchain, attacks on LSB, and a comparison study of EC and ElGamal with the RSA and SHA family is presented.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations